Advance care planning in patients referred to hospital for acute medical care: Results of a national day of care survey. (February 2020) - Knight, Thomas; Malyon, Alexandra; Fritz, Zoe; Subbe, Chris; Cooksley, Tim; Holland, Mark; Lasserson, Daniel
Abstract: Background: Advance care planning (ACP) is a voluntary process of discussion about future care between an individual and their care provider. ACP is a key focus of national policy as a means to improve patient centered care at the end-of-life. Despite a wide held belief that ACP is beneficial, uptake is sporadic with considerable variation depending on age, ethnicity, location and disease group. Methods: This study looked to establish the prevalence of ACP on initial presentation to hospital with a medical emergency within The Society for Acute Medicine Benchmarking Audit (SAMBA18). 123 acute hospitals from across the UK collected data during a day of care survey. The presence of ACP and the presence of 'Do Not Attempt Cardiopulmonary Resuscitation' orders were recorded separately. Findings: Among 6072 patients presenting with an acute medical emergency, 290 patients (4.8%) had an ACP that was available for the admitting medical team. The prevalence of ACP increased incrementally with age, in patients less than 80 years old the prevalence was 2·9% (95% CI 2·7–3·1) compared with 9·5% (95% CI 9·1–10·0%) in patients aged over 80. In the patients aged over 90 the prevalence of ACP was 12·6% (95% CI 9·8–16·0). ACP was present in 23·3% (95% CI 21.8–24.8%) of patients admitted from institutional care compared with 3·5% (95% CI 3·3–3·7) of patients admitted from home. The prevalence of ACP was 7.1% (95% CI 6·6–7·6) amongst patients re-admitted to the hospital within the previous 30 days. Interpretation: Very few patients have an ACP that is available to admitting medical teams during an unscheduled hospital admission. Even among patients with advanced age, and who have recently been in hospital, the prevalence of available ACP remains low, in spite of national guidance. Further interventions are needed to ensure that patients' wishes for care are known by providers of acute medical care.